Pengaruh Lama Waktu Biofermentasi Chromolaena Odorata dengan Sumber Karbon Tepung Putak Terhadap Produksi Gas Methan, pH, NH3 dan VFA In-vitro - Saefatu, Markus E.; Oematan, Gustaf; Lestari, Gusti A. Y.; Dami Dato, Twen O. (Animal Agricultura, 2025)
The aims of this study was to determine the effect of the length of time of Chromolaena odorata biofermentation with putak flour carbon source on methane production, pH, NH3 and Total VFA in-vitro. The main materials used were Chromolaena odorata, putak flour, and rumen fluid.  The method used was an experimental method with a completely randomised design (CRD) pattern consisting of 4 treatments and 4 replications. The treatments were LBf21 = 21 days biofermentation duration (as control); LBf14 = 14 days biofermentation duration; LBf7 = 7 days biofermentation duration; LBf0 = 0 days biofermentation duration. The variables studied were Methane Production, pH, NH3 and VFA in-vitro.  The results of statistical analysis on the variables of methane production, NH3 and total VFA showed that the treatment had no significant effect (P>0.05), while the pH value statistically showed that the treatment had a significant effect (P<0.05) on the length of time of biofermentation of Chromolaena odorata silage. It is concluded that the length of time of the biofermentation process has not been able to increase the production of total VFA, NH3, and reduce methane production but is able to increase the pH value of Chromolaena odorata silage silage from the biofermentation process.